The Role of Knowledge Heterogeneity on Business Performance: The Mediating Effects of Women's Technology Use and Innovation in East Java SMEs - Lucy Larassaty, Ayu (Universitas Nahdlatul Ulama Sidoarjo, 2025)
This study aims to analyze the role of knowledge heterogeneity on the business performance of women-owned SMEs in East Java, with mediation by technology use and innovation. This study uses a quantitative approach with an explanatory research design and data collection through a survey of 398 women-owned SMEs in 31 sub-districts in East Java. The analysis was conducted using SmartPLS to test the structural model and mediation effects. The results of the analysis indicate that knowledge heterogeneity has a positive effect on technology use and innovation, and both significantly mediate the effect of knowledge heterogeneity on business performance. These findings emphasize the importance of knowledge-based strategies in encouraging technology adoption and innovation to strengthen SME performance.